Azelastine Nasal Spray in Non-Hospitalized Subjects with Mild COVID-19 Infection: A Randomized Placebo-Controlled, Parallel-Group, Multicentric, Phase II Clinical Trial - Peter Meiser; Michael Flegel; Frank Holzer; Dorothea Groß; Charlotte Steinmetz; Barbara Scherer; Rajesh Jain; CARVIN-II Study Group (Viruses)
Nasal spray treatments that inhibit the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) entry into nose and nasopharynx at early stages can be an appropriate approach to stop or delay the progression of the disease. We performed a prospective, randomized, double-blind, placebo-controlled, parallel-group, multicentric, phase II clinical trial comparing the rate of hospitalization due to COVID-19 infection between azelastine 0.1% nasal spray and placebo nasal spray treatment groups. The study furthermore assessed the reduction in virus load in SARS-CoV-2-infected subjects estimated via quantitative reverse transcriptase polymerase chain reaction (RT-PCR) using nasopharyngeal swabs in both groups during the treatment period. A total of 294 subjects with mild COVID-19 infection were screened and randomized in a 1:1 ratio. There was no incidence of COVID-19-related hospitalization in either treatment group. Mean virus load was significantly reduced in both groups during the 11 treatment days as compared with baseline viral load values. The reduction in virus load in the azelastine 0.1% nasal spray group was significantly higher than the reduction in the placebo group at day 11 (log10 5.93 vs. log10 5.85 copies/mL, respectively, p = 0.0041). A total of 39 (32.0%) subjects in the azelastine 0.1% treatment group and 40 (31.0%) subjects in the placebo group reported 48 and 51 adverse events, respectively. It is therefore concluded that azelastine 0.1% nasal spray is an efficacious, safe, and well-tolerated treatment of mild COVID-19 infection.